The Effect of Open-ended Tasks –as an assessment tool-‎‏ ‏on Fourth ‎Graders’ Mathematics Achievement, and Assessing Students’ ‎Perspectives about it - Al-Absi ‎, Mohammad (Jordan Journal of Educational Sciences, 2013)
The open-ended task constitutes an effective type of assessment. This study aimed at investigating the effect of open-ended tasks on fourth graders’ mathematics achievement and assessing students’ perspectives about it. The sample of the study consisted of (135) fourth grade students, from four sections, distributed randomly to an experimental group who were assessed during the “9-digit Numbers” unit by exposing them to open-ended tasks, and a control group who were assessed using the traditional method of instruction. Results of the study revealed that open-ended tasks had a positive effect on improving students’ mathematics achievement, and assessing their perspectives toward using the tasks in learning mathematics